Measuring the Effect of Subject-Specific Pedagogy on TPACK through Flipped Learning in E-Learning Classroom - Widyasari, Frenika; Masykuri, Mohammad; Mahardiani, Lina; Saputro, Sulistyo; Yamtinah, Sri (International Journal of Instruction, 2022)
Technological pedagogical and content knowledge (TPACK) is an essential framework for chemistry teachers. Teachers are required to be able to integrate technology into learning so that TPACK must be acquired by pre-service chemistry teachers. TPACK can be integrated with a modified form of subject-specific pedagogy (SSP) as SSP has the same concept as PCK. In accordance, this study aims to measure the effect of using SSP through flipped learning on the pre-service chemistry teachers' TPACK. This research was conducted in Creswell's mixed-method. The subjects were 34 pre-service chemistry teachers from the chemistry education department in Indonesia. The data obtained from the pre-test and post-test were then analyzed by using Rasch's stacking-racking method. The result of this study indicated that pre-service chemistry teachers' ability (stacking method) from pre-test to post-test increased after being given the intervention. Then, the item analysis (racking method) showed that pre-service chemistry teachers found it easier to work on post-test items after being given the intervention. Based on the qualitative data, it was known that pre-service chemistry teachers could integrate technology with pedagogy and content in chemistry learning. It revealed that the intervention given during learning effectively affected the pre-service chemistry teachers' TPACK both in terms of personal ability and item difficulty level. Thus, strengthening TPACK since an early stage, as pre-service chemistry teachers, with specific treatments, could help them teach in real classrooms.